LARYNGEAL TUBERCULOSIS - A NEGLECTED DISEASE THAT CAN MIMIC LARYNGEAL CARCINOMA - Jovan JAVORAC (Rojan GÜMÜŞ, 2021)
Laryngeal tuberculosis is a form of extra-pulmonary tuberculosis that occurs in only 1% of all tuberculosis cases, with the mortality rate of less than 2%. It can be a complication of pulmonary or some other form of extra-pulmonary tuberculosis (via bronchogenic, haematogenic or lymphagenic spread of bacilli), or the larynx can be the only organ affected after the direct invasion of Mycobacterium tuberculosis. Clinical, laryngoscopic and radiological findings of laryngeal tuberculosis tend to mimic laryngeal cancer, delaying the appropriate treatment. In this paper, we present a case of the laryngeal and pulmonary tuberculosis which was primarily diagnosed and almost treated as laryngeal carcinoma. An 84 years old Caucasian male presented with a 3-months history of hoarseness, odynophagia, dysphagia, cough with expectoration and weight loss. After the laryngoscopy and biopsy of the laryngeal ulceration, a squamous cell carcinoma was suspected. However, chest X-ray and CT scan detected pulmonary infiltrates, while the positive sputum smear for acid-fast bacilli was obtained and the sputum cultures grew Mycobacterium tuberculosis. Detailed histopathological analysis of the biopsies was in accordance with tuberculosis, and no signs of timorous tissue were found. After the end of the proposed antituberculous treatment, the patient reported no symptoms of the diseases, laryngoscopic findings showed no signs of neoplastic tissue, and CT findings showed partial radiological regression. Distinguishing laryngeal carcinoma and tuberculosis can be very challenging, even after obtaining histopathological material. Nevertheless, biopsies should be taken from all suspicious lesions and at multiple sites and Ziehl-Neelson staining of sputum and bioptic tissue is necessary. Otorhinolaryngologists should always consider tuberculosis in differential diagnosis of laryngeal lesions, especially nowadays when the incidence of laryngeal tuberculosis is increasing in developing countries.